Antisite Defect‐Enhanced Thermoelectric Performance of Topological Crystalline Insulators. (6th July 2020) - Muzaffar, Muhammad Usman; Zhang, Shunhong; Cui, Ping; He, Jiaqing; Zhang, Zhenyu
Abstract: As the first experimentally established topological crystalline insulator (TCI), SnTe also exhibits superior thermoelectricity upon proper doping; yet to date, whether such doping will preserve or destroy the salient topological properties in achieving outstanding thermoelectric (TE) performance remains elusive. Using first‐principles calculations combined with Boltzmann transport theory, here the elegant role of antisite defect in optimally enhancing the thermopower of SnTe while simultaneously preserving its topological nature is uncovered. It is first shown that SnTe antisite defect effectively induces pronounced variations in the low‐energy density of states rather than rigidly shifting the chemical potential, resulting in a higher Seebeck coefficient and power factor. Next, it is demonstrated that in a wide temperature range, the Seebeck coefficient of antisite‐doped SnTe distinctly outperforms previously identified systems invoking extrinsic dopants. It is further confirmed that such intrinsic antisite doping preserves the nontrivial topology, which in turn favors high electrical conductivity and thermoelectricity. These central findings not only identify an effective and powerful knob in future studies of TE materials, but also help to resolve standing controversies between theory and experiment surrounding the TE performances of both TCIs and topological insulators. Abstract : Antisite defect engineering is introduced as a powerful strategy to effectively engineer band structure, resulting in optimally enhanced thermoelectric performance of SnTe while simultaneously preserving its topological nature. The present study sheds new light on the inherent ties between the thermoelectric and topological properties of various materials.